Thermal infra-red remote sensing for water stress estimation in agriculture - Labbé S.; Lebourgeois V.; Jolivot A.; Marti R. (The use of remote sensing and geographic information systems for irrigation management in Southwest Europe, 2012)
Thermal infrared images can be used to estimate vegetation water content of the plant and thus to locally adapt (precision agriculture) and globally adjust (sustainable management of water resources) irrigation water quantities. Thermal imaging cameras using micro-bolometer sensors loaded on light aerial vehicles are suitable to produce thermal images. These images are helpful for irrigation monitoring if they are: (i) coupled with simultaneous acquisition of images in the visible and near infrared bands; (ii) geometrically corrected to be superimposed with other images; and (iii) radiometrically corrected to take into account the drift of the thermal sensors and the effects of the atmosphere on the measured temperature.